LITERASI PEMBERDAYAAN PENDIDIKAN DAN KESETARAAN GENDER MELALUI WEBSITE NASYIATUL AISYIYAH KOTA TANGERANG SELATAN - Kristiyanti, Dinar Ajeng; Yuliani, SY; Pratiwi, Monica; Irmawati, Irmawati; Johan, Monika Evelin; Umam, Akhmad Hairul; Adiputri, Tresya Meisel; Audilia, Maureen (LPPM Universitas Nusa Mandiri, 2026)
Nasyiatul Aisyiyah Kota Tangerang Selatan (NA Tangsel) is a youth women's organization in Indonesia under the Muhammadiyah community organization whose administrators consist of young women aged 17-40 years whose activities focus on women, religion, society, and education who have actively supported gender equality and education through various programs. The problems faced by the NA Tangsel administrators are logistical challenges, funding, community resistance, and limited market reach, which affect the effectiveness of their programs to grow and advance in supporting education and gender equality. To overcome this, the community service (PKM) implementation team has collaborated with the NA Tangsel administrators to disseminate website technology that can be a solution to become a place for NA administrators to run their programs to be more independent, empowered with increased digital literacy, obtain sustainable income, and support advocacy and empowerment efforts. This initiative strengthens economic empowerment and family welfare through effective and efficient skills training and entrepreneurship programs. The method applied is Community Participatory Action Research (CBPAR), which combines knowledge and action in a way that involves NA Tangsel administrators as active partners in every stage of PKM activities. The results achieved were increased implementation of science and technology through digital skills and the effectiveness of NA management performance, as measured through pre-tests and post-tests, with the percentage rising from 87.5% to 100%.